Liprin-alpha has LAR-independent functions in R7 photoreceptor axon targeting. - Hofmeyer, K.; Maurel-Zaffran, C.; Sink, H.; Treisman, J.E. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
In the Drosophila visual system, the color-sensing photoreceptors R7 and R8 project their axons to two distinct layers in the medulla. Loss of the receptor tyrosine phosphatase LAR from R7 photoreceptors causes their axons to terminate prematurely in the R8 layer. Here we identify a null mutation in the Liprin-alpha gene based on a similar R7 projection defect. Liprin-alpha physically interacts with the inactive D2 phosphatase domain of LAR, and this domain is also essential for R7 targeting. However, another LAR-dependent function, egg elongation, requires neither Liprin-alpha nor the LAR D2 domain. Although human and Caenorhabditis elegans Liprin-alpha proteins have been reported to control the localization of LAR, we find that LAR localizes to focal adhesions in Drosophila S2R+ cells and to photoreceptor growth cones in vivo independently of Liprin-alpha. In addition, Liprin-alpha overexpression or loss of function can affect R7 targeting in the complete absence of LAR. We conclude that Liprin-alpha does not simply act by regulating LAR localization but also has LAR-independent functions.